The impact of conflict type on child and infant mortality rates: evidence from global data - Adan, Ubah Abdulgani (AUC Knowledge Fountain, 2012)
Wars kill, destroy, cause havoc and leave lasting impacts on the societies affected. Infants and children are particularly susceptible to these shocks. This thesis looked at whether there is a differential impact across different types of war (civil and international) on child mortality rates among children in different age groups (neonatal, post neonatal, infant, ages 1-5, and under-5). An unbalanced dynamic panel dataset, from 155 countries covering a period of 30 years (1970-1999) was used in this analysis. The empirical results showed that international war contributed more to the rise of neonatal mortality than did civil war. Conversely, civil war had a greater impact on post neonatal, infant mortality, ages 1 to 5 and under 5 mortality rates, than did international war. A robust analysis was conducted using dynamic panel data analysis, which showed that the relationship between infant and child mortality and conflict, holds. Policy recommendations are made to develop strategies for interventions in the reduction of neonatal mortality especially in the presence of international wars.